Characterization of laminar zones in the mid-gestation primate brain with magnetic resonance imaging and histological methods - Xiaojie eWang; David R. Pettersson; Colin eStudholme; Christopher D Kroenke; Christopher D Kroenke (Frontiers Media S.A., 2015)
Distinct populations of progenitor and postmitotic neural and glial cells are stratified in the fetal primate brain across developmentally transient tissue zones between the ventricular and pial surfaces. These zones were originally identified by light microscopy. However, it has subsequently been shown that various forms of magnetic resonance image (MRI) contrast can be used to distinguish layers of developing neural tissue in ex vivo, as well as in vivo (including in utero) conditions. Here we compare mid-gestation rhesus macaque tissue zones identified using histological techniques to ex vivo as well as in utero MRI performed on the same brains. These data are compared to mid-gestation fetal human brain MRI results, obtained in utero. We observe strong similarity between MRI contrast in vivo and post mortem, which facilitates interpretation of in utero images based on the histological characterization performed here. Additionally, we observe differential correspondence between the various forms of ex vivo MRI contrast and microscopy data, with maps of the water apparent diffusion coefficient providing the closest match to histologically-identified lamina of the nonhuman primate brain. Examination of histology and post mortem MRI helps to provide a better understanding of cytoarchitectrual chararacteristics that give rise to in utero MRI contrast.